THE CORRELATION OF FLUID INTAKE AND PHYSICAL ACTIVITY WITH ADOLESCENT CARDIORESPIRATORY FITNESS IN CIPADANG VILLAGE - Ramadhana Komala; Wiwi Febriani; Dian Isti Angraini; Andi Eka Yunianto (Majalah Kedokteran Sriwijaya, 2024)
Cardiorespiratory fitness is the ability of the heart, lungs, and blood vessels to supply oxygen to the cells to sustain physical activity. A systematic review and meta-analysis indicate that adolescents with poor cardiorespiratory fitness are at higher risk of obesity and cardiometabolic diseases in the future. This type of research is an observational study with a cross-sectional design. The target population in this study were adolescents aged 12-15 years in Cipadang Village, Pesawaran Regency. The minimum sample size for this study using the Slovin Formula is 66 respondents. The type of data collected in this study is primary data. Data were collected in two ways, namely by direct measurement and interview. Cardiorespiratory fitness test was measured using 20 meters shuttle run test. Calculation of fluid intake through direct interviews with quantitative methods using 2x24h food recall questionnaire and physical activity using the 2x24h physical activity level (PAL) questionnaire. Data were analyzed using Spearman Test. There were a correlation between fluid intake (p=0.016, r=0.422) and physical activity (p=0.001, r=0.648) with VO2max. The conclusion of this study is that there is a correlation between fluid intake and physical activity with the VO2max. Therefore, adolescents are expected to be able to control daily fluid intake and routinely do physical activity to improve cardiorespiratory fitness to avoid obesity and cardiometabolic diseases in the future.